Model Pembelajaran Contextual Teaching Learning dalam Pendidikan Agama Kristen untuk Meningkatkan Karakter Siswa Kristiani - Magdalena Elly Kurniawati (Sekolah Tinggi Teologi Torsina Surakarta, 2019)
This study aims to examine the effectiveness of the Contextual Teaching Learning (CTL) learning model through Christian Religious Education in improving the Christian character of students in Surakarta 4 Public Middle School. This research was motivated by the fact and condition of Christian students at Surakarta 4th Middle School who experienced a decline due to Christian character. This research applies a participatory research approach with mixed methods research design. Interviews, observations, FGDs, and questionnaires were used to collect qualitative and quantitative data. Experiments are used to prove the effectiveness of the model is statistically significant, while field observations and FGDs are used to obtain practical data significant impact of the model. This research is tested as an effective learning model to improve students' character, especially in terms of love, honesty, discipline, and responsibility. In qualitative results, it can be seen in the attitudes of students who want to carry out tasks without complaining, attend morning services, and are able to understand precisely the essence of Christian character. This research is recommended for curriculum vice principal, teachers, students, and future researchers to apply this model. That is because the CTL learning model has proven effective for improving the Christian character of junior high school students.AbstrakPenelitian ini bertujuan untuk menguji keefektifan model pembelajaran Contextual Teaching Learning (CTL) melalui Pendidikan Agama Kristen dalam meningkatkan karakter Kristiani siswa di Sekolah Menengah Pertama Negeri 4 Surakarta. Penelitian ini dimotivasi oleh fakta dan kondisi siswa Kristen di SMPN 4 Surakarta yang mengalami kemerosotan berkaitan dengan karakter Kristiani. Penelitian ini menerapkan pendekatan penelitian partisipatif dengan desain penelitian metode campuran. Wawancara, observasi, FGD dan angket digunakan untuk mengumpulkan data kualitatif dan kuantitatif. Eksperimen digunakan untuk membuktikan efektivitas model secara statistikal signifikan, sedangkan observasi lapangan dan FGD digunakan untuk memperoleh data secara praktikal signifikan dampak model. Penelitian ini teruji sebagai model pembelajaran yang efektif untuk meningkatkan karakter siswa, khususnya dalam hal kasih, kejujuran, kedisiplinan dan tanggungjawab. Dalam hasil kualitatif terlihat dalam sikap siswa yang mau melaksanakan tugas tanpa mengeluh, mengikuti ibadah pagi, dan mampu untuk memahami dengan tepat esensi dari karakter Kristiani. Penelitian ini direkomendasikan bagi wakasek kurikulum, guru, siswa dan peneliti selanjutnya untuk menerapkan model ini.Hal itu karena model pembelajaran CTL telah terbukti efektif untuk meningkatkan karakter Kristiani siswa SMP.